NUMERICAL MODELING OF EMBANKMENT ON THIN CLAY SOIL WITH GEOFOAM - Anggraini, Muthia; Pratikso,; Maizir, Harnedi (Journal of Applied Engineering Science, 2024)
Soft soils cause problems in road subgrades because they have low bearing capacity. Embankments on soft ground need to be identified and reviewed before construction starts. Various soil reinforcement techniques can be used to improve soft soil conditions. This research focuses on using geofoam material as an embankment on soft soil. The aim is to analyze the modeling of soft soil embankment with geofoam. The research method is a numerical method using the Plaxis 2D version 2023 application. There are two models in this study, namely the embankment model without geofoam, 100 cm thick subgrade, and the embankment model with 30 cm thick and 40 cm thick geofoam. The embankment geometry model is assumed to be symmetrical, hardening soil parameters are used to model soft soil for analyzing consolidation settlement, and elastic linear parameters to model geofoam. The type of FEM analysis in this research is plain strain. Numerical results at a maximum load of 100 kN showed a settlement of 0.1587 mm at 30 cm geofoam thickness and 0.1507 mm at 40 cm geofoam thickness. Deformation of 16 mm in 30 cm thick geofoam and 15.22 mm in 40 cm thick geofoam. Soil stress of 201 kN/m² in 30 cm thick geofoam and 192 kN/m² in 40 cm thick geofoamm. In conclusion, the model of embankment on soft soil with geofoam is that the thicker the geofoam used, the smaller the settlement and the stress on the soil that occurs.
Keywords: EPS22, soil reinforcement, 2D finite element, subgrade, clay